Endoscopist characteristics that influence the quality of colonoscopy - Jover, Rodrigo; Zapater, Pedro; Bujanda, Luis; Hernández, Vicent; Cubiella, Joaquín; Pellisé, Maria; Ponce, Marta; Ono, Akiko; Lanas, Angel; Seoane, Agustín; Marín-Gabriel, José C.; Chaparro, María; Cacho, Guillermo; Herreros-de-Tejada, Alberto; Fernández-Díez, Servando; Peris, Antonio; Nicolás-Pérez, David; Murcia, Oscar; Castells, Antoni; Quintero, Enrique; COLONPREV Study Investigators (Endoscopy, 2016)
Background and study aim: Several factors have been shown to be related to colonoscopy quality; however, little is known about the effects of endoscopist factors. This study analyzed the influence of endoscopist-related characteristics on quality indicators for colonoscopy.Patients and methods: The study included 48 endoscopists who each performed at least 20 colonoscopies in the colonoscopy arm of a randomized controlled trial comparing fecal immunochemical test vs. colonoscopy in colorectal cancer screening. These endoscopists performed a total of 3838 procedures in the trial. The following were calculated for each endoscopist: adenoma detection rate (ADR), advanced ADR, proximal ADR, distal ADR, and adenoma per colonoscopy rate (APCR). The characteristics of endoscopists were assessed with regard to colonoscopy quality using multivariate regression analysis. Endoscopist characteristics included age, sex, exclusive endoscopy practice, years as a physician, years as a specialist, specialty, total (life-long) number of colonoscopies performed, annual colonoscopy volume, number of hours/week dedicated to endoscopy and number of educational activities in the previous year. Results: Factors associated with ADR were age of the endoscopist (odds ratio [OR] 1.11, 95 % confidence interval [CI] 1.01 – 1.21; P = 0.01) and life-long number of colonoscopies (OR 1.06, 95 %CI 1.01 – 1.11; P = 0.01). Only exclusive dedication to endoscopy practice was found to be independently related to proximal ADR (OR 1.71, 95 %CI 1.15 – 2.74; P = 0.001). Life-long number of colonoscopies was independently related to detection of distal adenomas (OR 1.07, 95 %CI 1.01 – 1.13; P = 0.01). None of the analyzed endoscopist characteristics was associated with advanced ADR or APCR.Conclusions: This study found that the experience of the endoscopist and exclusive dedication to endoscopy practice, but not annual colonoscopy volume, were associated with better colonoscopy quality.